1982
DOI: 10.1021/ic00131a038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,1'-bicobaltocene salts of tetracyano-p-quinodimethanide and the structure of 1,1'-bicobaltocene[CoIIICoIII] tris(tetracyano-p-quinodimethanide)

Abstract: Die Reaktion von 1,1 ′‐Bicobaltocen[Co(III)Co(III)]‐bis[hexaf1uorophosphat] oder der analogen gemischtwertigen [Co(III)Co(II)]‐Verbindung mit Triethylammonium‐bis‐ [tetracyano‐p‐chinodimethanid] im Überschuß und neutralem Tetracyano‐p‐chinodimethan liefert die diamagnetische Titelverbindung (89% Ausb.), deren Kristallstruktur (Raumgruppe P1, Z=1) bestimmt wurde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…The distances between the planes of the TCNQ moieties are between 3.25 Å for BC and 3.30 Å for AB . This is what is expected for van der Waals stacking of aromatic rings and what is observed also for other CT complexes with TCNQ. ,,, The molecular planes are almost parallel, with interplanar angles of 0.3° for BC and 3.30° for AB . There are two crystallographically independent ferrocenium cations, X and Y , the iron atom of the latter being placed on a symmetry center.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The distances between the planes of the TCNQ moieties are between 3.25 Å for BC and 3.30 Å for AB . This is what is expected for van der Waals stacking of aromatic rings and what is observed also for other CT complexes with TCNQ. ,,, The molecular planes are almost parallel, with interplanar angles of 0.3° for BC and 3.30° for AB . There are two crystallographically independent ferrocenium cations, X and Y , the iron atom of the latter being placed on a symmetry center.…”
Section: Resultssupporting
confidence: 83%
“…In general, depending on the redox potential and the steric demand of the donor molecules, TCNQ-containing complexes show different stoichiometries (donor-to-acceptor ratio), such as 1:1, 1:2, , 1:3, , 1:4, , and 2:5, although other proportions have been observed. Several organometallic derivatives containing TCNQ or TCNQF 4 have also been reported. ,− These materials turn out to be either insulators (e.g., the 1:1 salts containing ammonium cations) or semiconductors (e.g., the mixed valent 1:2 or 1:3 complexes with ferrocenium cations 2,7 ); alternatively they show metallic character (e.g., (TTF)(TCNQ) or (TSeF)(TCNQ)), as reported in excellent review articles concerning conducting organic compounds. , On the other hand, compounds with interesting magnetic properties (normal paramagnets, metamagnets, , but also low-temperature ferromagnets ,, ) have been found.
1
…”
Section: Introductionmentioning
confidence: 94%
“…123,124 Little information is available from binuclear cobalt sandwiches: the mixed-valence monocation of bis(fulvalene)dicobalt has been briefly mentioned. 125 The isomeric bications 9 and 10 have been made by Hendrickson,126 and polarographic studies have led to the proposal of intermediacy of mixed-valence monocationic species for each series:127 However, later CV studies57 showed that only the fulvalene series can give rise to mixed valency. Reduction of the biphenyl complex proceeds directly by a fast 2e step at -30 °C on a Pt or Hg cathode in DMF.…”
Section: Blnuclear 37e and 38e Complexesmentioning
confidence: 99%
“…In the 1930s, Hieber pioneered the studies of the disproportionation of metal carbonyl dimers. 183,277 Many of these thermal and photochemical reactions proceed according to M2(CO)2" + mL -[M(CO)n_m+1LJ+,[M(CO)"]- (125) After the first kinetic studies by Heck278 on Co(C-0)4SnCl3, it was recognized by Brown279-281 that the disproportionation of metal carbonyl dimers follows a radical chain pathway strongly influenced by the stereoelectronic properties of the added ligand L. This radical chain pathway resembles ETC-catalyzed reactions. In some cases, these reactions have indeed been directly initiated by added reducing agents.…”
Section: Disproportionationmentioning
confidence: 99%
“…charge derived from stoichiometry) of TCNQ is À1/2 (Ashwell et al, 1977a(Ashwell et al, , 1982. Pancake-bonded trimers, which often form stacks, are quite common, with a formal charge on the TCNQ À moiety of À2/3 (Ashwell et al, 1977b;Endres et al, 1978a,b;Ashwell & Wallwork, 1979; Sandman et Lau et al, 1982;Bell et al, 1991;Usov et al, 1991;Akutagawa et al, 1996Akutagawa et al, , 2004Bigoli et al, 1996;Ballester et al, 2000;Nishijo et al, 2004;Chen et al, 2007;Liu et al, 2008;Mochida et al, 2008;Martin et al, 2012;Kubota et al, 2014;Phan et al, 2015). However, different bond lengths in the central and lateral rings of a trimer indicate different total charge of the rings, which can be estimated using geometric correlations (see above).…”
Section: Introductionmentioning
confidence: 99%